Developing 4C skills through scientific writing for labor readiness - Suryani, Ani Wilujeng; Larasati, Ika Putri; Harliansyah, Prastiawan; Faurehzi, Novrico Putra; Novia, Sanny Sheilla; Sabrina, Diana Maulia (Universitas Muhammadiyah Magelang, 2025)
The evolving demands of the labor market require technical skills, critical thinking, creativity, collaboration, and effective communication skills (4C skills). One supporting aspect of 4C skills is writing ability, which can assist students in effectively presenting information, expressing opinions, and communicating well. This community service activity aims to improve students’ ability to produce quality scientific writing, develop 4C skills, and contribute to reducing unemployment through readiness to face the labor market. The workshop implementation method includes a preparation stage, an online workshop stage, and an evaluation stage. The results of the pre-test (M=80.00, SD=12.06) and post-test (M=87.83, SD=10.85) showed a p-value <0.001, indicating that the workshop activity successfully increased participants’ knowledge and understanding of good scientific writing.